1989
DOI: 10.1002/macp.1989.021901218
|View full text |Cite
|
Sign up to set email alerts
|

In‐situ photopolymerization of oriented liquid‐crystalline acrylates, 4. Influence of a lateral methyl substituent on monomer and oriented polymer network properties of a mesogenic diacrylate

Abstract: Mesomorphism and the molecular orientation of 1,4‐phenylene bis{4‐(6‐(acryloyloxy)hexyloxy)benzoate} (1) and its derivative with a methyl‐substituent in the central phenylene group (2) are studied. The methyl group affects the transition temperatures and the thermodynamic parameters, but not the order parameter of the monomers. The photoinitiated polymerization of the diacrylate monomers in their uniaxially oriented state leads to highly oriented and densely crosslinked polymer networks. The order parameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(97 citation statements)
references
References 27 publications
4
92
1
Order By: Relevance
“…In contrast, for nematic liquid-crystalline diacrylate 1 it has been reported that the order remains constant or even increases upon polymer formation, depending on the polymerization temperature. [21] The strong reduction (65 %) in the dichroic ratio can, in principle, be caused by photoisomerization of the azo dye upon irradiation with UV light. In a control experiment diacrylate 3, doped with 2 wt % dye 4 and 0.1 wt % inhibitor, is subjected to 365 nm UV irradiation in absence of the photoinitiator to prevent photopolymerization.…”
mentioning
confidence: 99%
“…In contrast, for nematic liquid-crystalline diacrylate 1 it has been reported that the order remains constant or even increases upon polymer formation, depending on the polymerization temperature. [21] The strong reduction (65 %) in the dichroic ratio can, in principle, be caused by photoisomerization of the azo dye upon irradiation with UV light. In a control experiment diacrylate 3, doped with 2 wt % dye 4 and 0.1 wt % inhibitor, is subjected to 365 nm UV irradiation in absence of the photoinitiator to prevent photopolymerization.…”
mentioning
confidence: 99%
“…This is expected since the N2 has fewer flexible carbons and is a stiffer molecule. Broer et al [7] measured Tg of the N1 using the loss tangent from dynamic mechanical analysis. They found that the transition region was very broad with a peak at approximately 90~ It is not completely clear where Tg should be assigned in the birefringence data of Figs 3 and 4, however the peak of the curve for N1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The N1 has 6-carbon aliphatic spacers on each side of the core while the N2 has 3-carbon spacers. N 1 has been studied extensively by Broer et al [7].…”
Section: E X P E R I M E N Tmentioning
confidence: 99%
“…8 However the value of E is much lower than that measured for similar materials in bulk systems. 12 We attribute this to a number of factors: ͑1͒ polymerization was carried out on the pore surface of the Anopore membrane, resulting in the system that is very different from bulk, ͑2͒ lecithin used for alignment certainly acts as a plasticizer which reduces cross linking, and ͑3͒ swelling of the polymer by the solvent decreases the glass transition temperature which enables switching. In the absence of solvent switching does not occur which supports the swelling hypothesis.…”
Section: ͑4͒mentioning
confidence: 99%